1998
DOI: 10.1007/s001670050095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the vastus medialis obliquus on the patellofemoral joint

Abstract: In this study, the effect of dynamic stabilizers on the patellofemoral (PF) joint was investigated in normal volunteers (group I) and in patients with patellar pain (group II) or instability (group III) by using computed tomography (CT) analysis and integrated electromyography (iEMG) of the quadriceps muscle. Nine subjects (16 knees) from group I, 10 patients (12 knees) from group II and 8 patients (12 knees) from group III were included in the study. CT scans of the PF joint with quadriceps contracted (QC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
(110 reference statements)
1
38
1
2
Order By: Relevance
“…The present study was performed with the quadriceps relaxed, and this may explain the absence of differences between the groups because, in Taskiran et al 33 , the PTA was lower with the quadriceps contracted in individuals with patellofemoral instability in relation to the control group. In contrast, Kujala et al 5 evaluated the PD in a control group during knee extension MVICs and compared the images with the quadriceps relaxed, finding no difference between them.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The present study was performed with the quadriceps relaxed, and this may explain the absence of differences between the groups because, in Taskiran et al 33 , the PTA was lower with the quadriceps contracted in individuals with patellofemoral instability in relation to the control group. In contrast, Kujala et al 5 evaluated the PD in a control group during knee extension MVICs and compared the images with the quadriceps relaxed, finding no difference between them.…”
Section: Discussionmentioning
confidence: 71%
“…These results showed, therefore, that the patellar position was not correlated to the electrical activity. Taskiran et al 33 used computed tomography to analyze the PTA of the knee and EMG to analyze the VMO and VL in nine normal subjects (G1), 10 with knee pain (G2) and 8 with patellar luxation (G3). The results showed a decrease in PTA in G1 and an increase in G2 and G3 during quadriceps contraction at 0°, 15° and 45° of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Thus, precise coordination of the activity of the vasti is important in control of the patellofemoral joint. A number of studies have reported that the ratio of the EMG activity of VMO relative to VL in people without knee pain is approximately 1:1 throughout knee range of movement, [26][27][28][29] and that the relative onset of VMO and VL EMG is simultaneous in people with no knee pain during functional tasks. 18,26,30,31 Furthermore, a change in relative onset of activity between these muscles has been associated with dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…18,26,30,31 Furthermore, a change in relative onset of activity between these muscles has been associated with dysfunction. For example, people with PFP have a reduced VMO:VL ratio, 29 and the onset of VMO EMG activity is delayed relative to VL in functional tasks. 18,30 The present data are consistent with the majority of studies that report no effect of knee angle on activity of the vasti muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation